2006
DOI: 10.1167/iovs.05-0580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Proliferation of Human Retinal Endothelial Cells under In Vitro Conditions

Abstract: These data suggest an underlying mechanism whereby curcumin induces the apoptosis in HRECs by the regulation of intracellular ROS generation, VEGF expression and release, and VEGF-mediated PKC-betaII translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…However, the effect of high glucose on the proliferation of HRECs found in these studies has varied. Yuan et al demonstrated that treatment of HRECs with 30 mM glucose for 48 h increased the proliferation of HRECs compared with 5 mM glucose treatment (18), while two other studies indicated that treatment with 30 mM glucose for 24 and 72 h failed to increase the proliferation of HRECs (20,22). Differences in cell lines and culture times have been suggested as a cause of the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of high glucose on the proliferation of HRECs found in these studies has varied. Yuan et al demonstrated that treatment of HRECs with 30 mM glucose for 48 h increased the proliferation of HRECs compared with 5 mM glucose treatment (18), while two other studies indicated that treatment with 30 mM glucose for 24 and 72 h failed to increase the proliferation of HRECs (20,22). Differences in cell lines and culture times have been suggested as a cause of the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…15 Sameermahmood et al 16 demonstrated that human retinal endothelial cell (HREC) treated with 30 lM of curcumin inhibited SDF-1a-induced cell migration through blockage of Ca 2þ influx and reduction of PI3K/AKT signaling. Premanand et al 17 also indicated 10 lM of curcumin induced the HRECs apoptosis partly by the control of iROS production. Bian et al 18 reported that 20 lM of curcumin effectively reduced glycated human serum albumin-induced IL-8 and MCP-1 secretion in human RPE cells.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies using HRECs, but not other endothelial cells, have obtained similar results to those of the present study. Premanand et al (19) failed to identify an increase in cell proliferation following high glucose (30 mM) exposure in HRECs, despite observing an increased expression of vascular endothelial growth factor (VEGF). This finding is consistent with the results of the present study indicating cell proliferation under high glucose …”
Section: Discussionmentioning
confidence: 99%